Dentigerous cyst associated with impaction of right maxillary third molar on panoramic radiograph and CBCT: a case report - Anak Agung Istri Agung Feranasari; Ida Bagus Nyoman Dhedy Widyabawa (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2023)
Objectives: The aim of this case report is to description of a dentigerous cyst associated with impaction of right maxillary third molar on panoramic radiographs and cone-beam computed tomography (CBCT). Case Report: A 61-year-old male patient came to the Radiology Installation of RSGM Saraswati Denpasar to do perform a panoramic radiograph examination of tooth 15 which had cavities, pain and swelling of the upper right cheek. The results of panoramic radiograph examination showed tooth 15 had caries reaching the pulp and there was a radiolucent lesion at the apikal tooth 15, there was a radiolucent lesion from the mesio-distal CEJ on the crown of the maxillary right third molar that had not erupted, the borders were well-defined, corticated, unilocular, involving the apical of teeth 15,16 and 17. A few days later the patient came back to do CBCT to see more clearly the boundaries, diameter of the lesion and see the relationship of the lesion with surrounding structure. Conclusion: Panoramic radiography and CBCT can be used as a supporting examination in making a diagnosis. The dentigerous cyst associated with impacted right maxillary third molar is clearly visible on the panoramic radiograph and CBCT so that it can assist in planning the appropriate treatment for the patient.